Smart Toolkit for Evaluating Information Projects, Products and Services: Second Edition: Part II The Evaluation Process - Technical Centre for Agricultural and Rural Cooperation; Inter-American Institute for Cooperation on Agriculture; Royal Tropical Institute (Technical Centre for Agricultural and Rural Cooperation, 2009)
In Part 2, we move on to the evaluation process itself. This process can be grouped into four phases: preparing the evaluation terms of reference, designing the evaluation, implementing the evaluation, following up the evaluation